Wild Honey Intoxication: A Case Series From Nepal - Rukma Raj Kafle; Rakshya Arun Kandel; Sabin Chaulagain; Angela Basnet; Shiva Kumar Ojha; Alok Atreya (Clinical Case Reports)
ABSTRACT Wild honey poisoning can cause serious cardiovascular complications, including bradycardia and hypotension, even with small amounts (1–2 teaspoons) consumed. Symptoms typically emerge within 30–45 min of ingestion. Early intervention with IV fluids and atropine is effective in most cases, but severe cases may require vasopressors, particularly when presentation is delayed.